Evaluating the Impact of a Mobile Application on Mental Health and Help-Seeking Behaviour among Adolescents in Bandung, Indonesia - Purnama, Heni; Ibrahim, Masdum; Juniarni, Lia; Lindayani, Linlin (The Malaysian Journal of Nursing (MJN), 2025)
Background: Mobile applications offer promising tools to promote mental health awareness and engagement, but their effectiveness in fostering help-seeking behaviour, particularly in Indonesia, remains underexplored. This study evaluated the effectiveness of a mobile application in enhancing help-seeking behaviour among adolescents in Bandung, Indonesia. Methods: A quasi-experimental pre- and post-test control group design was employed. A total of 200 adolescents aged 15–18 years were divided into intervention (n = 100) and control (n = 100) groups. The intervention group utilised a mental health mobile App with interactive health education and reminders systems for eight weeks, while the control group received mental health education pamphlets. Help-seeking behaviour was assessed using the Help-Seeking Behaviour Questionnaire (HSBQ) pre- and post-intervention. Regression analysis controlled for baseline scores and demographics. Results: The intervention group demonstrated significant improvements in help-seeking behaviour compared to the control group (B = 2.10, p < 0.001), independent of baseline scores. Conclusion: The findings highlight the potential of mobile applications to enhance help-seeking behaviour among adolescents, addressing critical barriers such as stigma and lack of awareness. Further research is needed to evaluate long-term sustainability and scalability on diverse populations.